Oscillatory MHD convective flow of second order fluid through porous medium in a vertical rotating channel in slip-flow regime with heat radiation - Garg, B.P.; Singh, K.D.; Bansal, A.K. (Zielona Góra: Uniwersytet Zielonogórski)
An analysis of an oscillatory magnetohydrodynamic (MHD) convective flow of a second order (viscoelastic), incompressible, and electrically conducting fluid through a porous medium bounded by two infinite vertical parallel porous plates is presented. The two porous plates with slip-flow condition and the no-slip condition are subjected respectively to a constant injection and suction velocity. The pressure gradient in the channel varies periodically with time. A magnetic field of uniform strength is applied in the direction perpendicular to the planes of the plates. The induced magnetic field is neglected due to the assumption of a small magnetic Reynolds number.
Keywords: slip-flow; convective; porous medium; rotating; oscillatory; radiation; second order fluid